Molecular marker analysis of spike fertility index and related traits in a bread wheat recombinant inbred line population - Panelo, Juan Sebastián (2019)
Spike fertility index (SF) has been well established as an ecophysiological trait related to grain number per unit area and a promising selection target in wheat breeding programs. Scarce information on the molecular basis of SF is available thus far. In this study, a preliminary molecular marker analysis was carried out in a RIL population derived from the cross between two Argentinean cultivars with contrasting SF to identify candidate genomic regions associated with SF. Twenty-four microsatellites and two functional markers that had been found to co-segregate with SF in a bulked-segregant analysis of the F3 generation of the population were analyzed. Phenotypic data were collected from three field experiments carried out during 2013, 2014 and 2015 growing seasons at Balcarce, Argentina. Two genomic regions associated with SF in chromosomes 5BS and 7AS were detected, which merit further investigation.